MODEL PERTANGGUNGJAWABAN HUKUM DANA BANTUAN ORANG TUA MURID PADA RSBI (STUDI KASUS SMPN RSBI DI KABUPATEN BOYOLALI) - Marlina, Titin; Harun, Harun; Subekti, Natangsa (Universitas Muhammadiyah Surakarta, 2013)
The objective of this study was to identify the model of legal liability for the budget from the studentsâ parents in the international program of state junior high school level. The specific obtives of this study include three issues, namely: (1) the implementation of legal liability model for budget management derived studentsâ parents, (2) the compli- ance of legal liability model with the normative provisions rule of Regional autonomy legislation, education system law, and the provision of local financial management, (3)Â how to formulate the legal liability model is so applicable and in accordance with the provisions. This research was conducted at SMPN I and II Boyolali. The data analysis technique used was descriptive and predictive. The research findings are as follows: ( 1) there is no basic standards in the financial management legislations, ( 2) management of the funds do not have compliance with the rules of regional autonomy laws, and provision of local financial management, (3) the legal liability model used is a model of financial management in one way through the establishment of local regulation on APBD and accountability of budget legislation (APBD) by the Bupati, which is based on the involvement of parents partisipation either directly or through a committee, in the plan- ning stages.